Structural and A.C. Conductivity Studies of (PVdF + NaClO4) Solid Polymer Electrolyte System for an Electrochemical Cell Applications - Sunita Sundari, G.; Vijaya Kumar*, K.; Krishna Jyothi, N.; Anji Reddy, P. (Asian Journal of Chemistry, 2013)
An investigation is carried out on a new solid polymer electrolyte system consisting of poly(vinylidene fluoride) (PVdF) as a host polymer, sodium perchlorate, as salt. Solid polymer electrolyte films were prepared by solution-casting technique and characterized by using IR, DSC, composition-dependence conductivity and transference number studies. IR studies revealed that the complexation of the polymer poly(vinylidene fluoride) with NaClO4. Differential scanning calorimetery was used to determine the melting temperatures of the pure and complexed films. The maximum ionic conductivity for 60 PVdF + 40 NaClO4 polymer electrolyte system was found to be 1.78 × 10-5 S/cm at room temperature. Transference number data suggests that the charge transport in this polymer electrolyte system is mainly due to ions. Electrochemical cells were fabricated with the configuration of Na+/(PVdF+NaClO4)/(I2+C+electrolyte) and discharge characteristics were studied under a constant load of 100 KW. Various cell parameters, such as open circuit voltage, short circuit current, power density and energy density were determined.